Analisis Strategi Pasar dan Pemasaran pada bisnis Waroeng Makan Si Engkong Pandawa - ROHIM, Muhammad (Maliki Interdisciplinary Journal, 2025)
This research aims to analyze market potential, competition, market share and marketing strategy of Warung Si Engkong Pandawa, a culinary business in Malang City. The method used is descriptive qualitative through interviews and direct observation. The research results show that Warung Si Engkong Pandawa has a large market opportunity with the main target being students and a strategic location near the main road. In facing competition, this business offers competitive advantages such as superior product quality, affordable prices, and efficient pre-order services. Marketing strategies through social media and the use of digital payment technology increase promotional reach and consumer convenience. Based on the evaluation, the market and marketing aspects of this business were declared feasible with an average score of 4.4. To maintain and increase consumer loyalty, it is recommended that businesses continue to improve innovation, product quality and value that differentiates them from competitors.